Extracellular superoxide dismutase, a molecular transducer of health benefits of exercise - Yan, Zhen; Spaulding, Hannah R. (Redox biology, 2020)
Extracellular superoxide dismutase (EcSOD) is the only extracellular scavenger of superoxide anion (O2.-) with unique binding capacity to cell surface and extracellular matrix through its heparin-binding domain. Enhanced EcSOD activity prevents oxidative stress and damage, which are fundamental in a variety of disease pathologies. In this review we will discuss the findings in humans and animal studies supporting the benefits of EcSOD induced by exercise training in reducing oxidative stress in various tissues. In particularly, we will highlight the importance of skeletal muscle EcSOD, which is induced by endurance exercise and redistributed through the circulation to the peripheral tissues, as a molecular transducer of exercise training to confer protection against oxidative stress and damage in various disease conditions.